СУБЪЕКТ ВОСПРИЯТИЯ: СООТНОШЕНИЕ АКТИВНОСТИ И ПАССИВНОСТИ - РЯБУШКИНА, Татьяна Михайловна (Гуманитарные исследования в Восточной Сибири и на Дальнем Востоке, 2023)
The article presents a critical analysis of the transcendental-phenomenological understanding of perception as a result of the active synthetic activity of the subject, aimed at the «matter» of experience acquired through passivity. This subjectivist view is compared with the phenomenological description of perception as being-in-the-world on the basis of ideas about embodiment and temporality. The author attempts to resolve the difficulties of these approaches by taking into consideration the preconscious process of cognition as a necessary condition for the possibility of conscious perceptions.